PEMBELAJARAN BAHASA INGGRIS BERBASIS LOCAL WISDOM DI GENIUS OPERATION KALANGANYAR SEDATI - Farin, Ade; Pujianto, Wahyu Eko (Abdi Pandawa: Jurnal Pengabdian Kepada Masyarakat, 2024)
English is a world language and the language most often used in international communication. Therefore, it is very important for children to start learning English from a young age to equip them with the skills needed to compete in the future. In addition, it is very important to incorporate local wisdom into teaching English. This activity takes place at Genius Operation Kalanganyar because in Kalanganyar Village there is potential for local wisdom. The purpose of this service is to apply local wisdom in learning English. This type of report uses qualitative and descriptive methods. Data collection techniques include observation, interviews, class action, and documentation. The subject of this service is the children participating in the Genius Operation tutoring which takes place in Kalanganyar Village, Sedati District. The results of this dedication show that this local wisdom-based learning can improve their understanding of English material because the material provided is not far from the surrounding life. The hope for this local wisdom-based learning is that children do not feel bored while learning and are more active in learning activities.